What is the Diagnosis? - Vasconcelos, J. Tarcísio Medeiros d (JOURNAL OF CARDIAC ARRHYTHMIAS, 2020)
One image and tracings were obtained during the para-Hisian stimulation maneuver in an electrophysiological study. The question is: is there any retrograde nodal or extranodal conduction behavior